2002
DOI: 10.1002/pros.10125
|View full text |Cite
|
Sign up to set email alerts
|

Both retinoids and androgens are required to maintain or promote functional differentiation in reaggregation cultures of human prostate epithelial cells

Abstract: A combination of retinoids and androgens is able to preserve, for a prolonged period of time, some degree of secretory differentiation in freshly isolated PEC maintained in reaggregation culture. The same combination is unable to restore secretory differentiation in subcultured PEC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…4A), suggesting that removing EGF was not sufficient to promote differentiation. We then supplemented EGF‐deficient culture medium with a cocktail of factors that have shown differentiating activity in prostate and other types of cells (Peehl et al, 1993; Danielpour, 1999; Zhao et al, 1999; Goossens et al, 2002). The individual factors in the cocktail, designated as “VRT,” were 1,25‐dihydroxyvitamin D 3 (10 nM), all‐trans retinoic acid (1 μM) and TGF‐β1 (1 ng/ml).…”
Section: Resultsmentioning
confidence: 99%
“…4A), suggesting that removing EGF was not sufficient to promote differentiation. We then supplemented EGF‐deficient culture medium with a cocktail of factors that have shown differentiating activity in prostate and other types of cells (Peehl et al, 1993; Danielpour, 1999; Zhao et al, 1999; Goossens et al, 2002). The individual factors in the cocktail, designated as “VRT,” were 1,25‐dihydroxyvitamin D 3 (10 nM), all‐trans retinoic acid (1 μM) and TGF‐β1 (1 ng/ml).…”
Section: Resultsmentioning
confidence: 99%
“…Three‐dimensional aggregates are considered to be superior to monolayer cell cultures in terms of communication between cells and maintenance of tissue‐specific gene expression in a variety of organs (61–67). In the present study, we compared cell type distribution in the aggregates with that of the 14‐day‐old rat pituitary gland.…”
Section: Discussionmentioning
confidence: 99%
“…These cells are typified by proliferation and simultaneous expression of markers of both basal and secretory cells, and are believed to be progenitor cells in the process of differentiating [Bonkhoff et al, 1994]. Analyses of additional markers of basal and secretory cells have shown that, indeed, primary cultures are populated by cells that have characteristics of both types of cells [van Leenders et al, 2000;Liu and Peehl, 2001;Goossens et al, 2002;Tran et al, 2002;Garraway et al, 2003].…”
Section: Cytokeratinsmentioning
confidence: 94%